2020
DOI: 10.1186/s13256-020-02565-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of low-molecular-weight heparin in severe paraquat poisoning: a case report

Abstract: Background Acute paraquat ingestion remains a leading cause of mortality in developing countries. There is currently no evidence that treatment with high-dose immunosuppressants and antioxidants improves survival in patients with paraquat poisoning, and better options are urgently needed. Here, we describe the unexpected survival and recovery of a patient with a potentially fatal paraquat poisoning. Case presentation After ingesting 28 mL of paraquat (20% ion w/v), confirmed by a deep blue color in the urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a sheep model of pneumonia and smoke inhalation induced lung injury, inhaled heparin significantly reduced lung vascular leak compared to systemic heparin administration. 23 Montoya Giraldo et al 24 reported a case of severe paraquat toxicity unexpectedly survived due to the addition of enoxapene, a low molecular weight heparin with the standard treatment. From these findings, we hypothesize that inhalation antithrombin therapy in the exudative phase of acute paraquat poisoning may reduce lung vascular leakage and fibrin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…In a sheep model of pneumonia and smoke inhalation induced lung injury, inhaled heparin significantly reduced lung vascular leak compared to systemic heparin administration. 23 Montoya Giraldo et al 24 reported a case of severe paraquat toxicity unexpectedly survived due to the addition of enoxapene, a low molecular weight heparin with the standard treatment. From these findings, we hypothesize that inhalation antithrombin therapy in the exudative phase of acute paraquat poisoning may reduce lung vascular leakage and fibrin deposition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that paraquat is concentrated in the alveolar epithelium of the lung. Small amounts, even if taken from the stomach or spat out, may still lead to asphyxiation from fibrous tissue in the lungs, even if they are eliminated from the body [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%